DOG HAIR SASHES FROM OBELISK CAVE. (May 2014) - Freer-Waters, Rachel A.; Jacobs, Mike
<x content-type="archive" xml:space="preserve">Abstract</x> A woven sash, previously described as made with dog hair yarn, has been identified as containing a combination of dog hair yarns and cotton yarns. The sash was one of six discovered by Earl Morris in 1931 at Obelisk Cave, a site with a predominantly Basketmaker III period (AD 500–750) occupation. Further investigation into the sashes revealed new insight into the materials used, and indicates a later date in the Pueblo I era.